Penataan Ruang Pamer Kerajinan Keramik Dinoyo Malang - Suryasari, Noviani; Mustikawati, Triandriani (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
Dinoyo ceramic village located on Jl. MT Haryono Dinoyo District of Dinoyo is a center of home industry economic activity, announced by the Government of the tourist village of Malang. Industrial products are produced is in the form of ceramics, with a wide variety of forms such as pottery items for decoration, various souvenirs to household appliances/ kitchen. On the one hand, the potential for the development of economic activities of the people of the industry is still quite large visible from a good level of marketing, not only in the city of Malang, but even out of town or country. But on the other hand, problems arise in the aspect of the promotion strategy that is not supported by quality of showroom with attractive layout concepts. Based on three deficiencies can be identified from the management arrangement ceramics Dinoyo showrooms are associated with: (1) space zoning (2) arrangement of physical elements of space and (3) arrangement of handicrafts, the community service is targeted to structuring concept showroom ceramics. Structuring concept was applied in the field by applying spatial organization in a more effective, and the provision of furniture in accordance with the character of the object to show off.Keywords: showrooms, ceramic